Comparative study of parasitic infestation between ducks reared in closed house system and open house free range system - Halil, Nur 'Izzaty (2015)
Parasitic infestation of commercial Pekin duck from closed house and open house free range system were investigated. A total of 16 matured ducks, 8 from each different rearing system was randomly selected; blood and feather samples were collected before slaughtered, and the intestinal content were collected immediately after slaughtering process in the slaughter house. A total of 48 fresh fecal samples from the floor were taken, 24 each from different rearing system. Thin blood smear stained with Giemsa shows negative result against Leucocytozoon sp. The feather was examined under dissecting microscope and shows negative result for ectoparasite. Simple floatation of the intestinal content shows negative result for helminth and its egg but fecal sample shows positive result for helminths. The present study shows that, there is no significant difference of prevalence of parasitic infestation in closed house and open house free range system of Pekin duck.